PENGARUH EXPERIENTIAL MARKETING STRATEGY TERHADAP KEPUASAN KONSUMEN (Studi Pada Konsumen Waroeng Steak and Shake Ciliwung Kota Malang) - Ahmad Fadeli; Rois Arifin; M Hufron (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTThe purpose of this study is to determinated the effect of experiential marketing variables on customer satisfaction in the steak and shake ciliwung warung Malang. The research method used is quantitative. Population and samples used in this research is customer waroeng steak and shake ciliwung Malang. Sampling technique using accidental sampling technique, while data analysis method used in this research is multiple linear regression analysis. The results of this study provide empirical evidence that experiential marketing variables both simultaneously and partially have a positive and significant impact on customer satisfaction.Keywords: experiential marketing and consumer satisfaction.